PERANCANGAN GRIPPER PADA LENGAN ROBOT PEMINDAH BAHAN TIPE CARTESIAN COORDINATE - Atmaja, Muhammad Iqbal; Hartono, Budi; Waluyo, Roy (ALMIKANIKA, 2019)
Based on Survey result from International Federation of Robotics (IFR) published a study of robots in the world. In this analysis, the institution summarized the results of the Growth of Industrial Robots around the world in the period 2003 - 2004, on average each year it increased by around 6% to 1,000,000 robots used to assist industrial processes. Gripper Arm Robot uses a robotic manipulator as an end effector. Previously there were people who made but different types. Arm Robot Gripper 5 DOF (Degree Of Freedom) has a main part, namely frame construction using Aluminum 1060, the drive system with MG 995 Servo with 10 Kgcm of torque needed to grip objects with a mass variation of 1000 grams, 600 grams and 300 grams on Gripper Arm Robot 5 DOF gets torque of 6.96 kgcm, 3.5 kgcm and 2 kgcm. Arm DO 5 Robot Gripper has style analysis, from force analysis can be found the stress on the rod is 0.546 ???????????? in the normal force of 8.19 N. From all the construction and driving systems there is a Robot Arm DOF 5 Grip can be concluded safe to use until the maximum load amounting to 1000 grams.